Simultaneous estimation of detection sensitivity and absolute copy number from digital PCR serial dilution. (June 2017) - Deng, Xutao; Custer, Brian S.; Busch, Michael P.; Bakkour, Sonia; Lee, Tzong-Hae
Abstract: Digital polymerase chain reaction (dPCR) is a refinement of the conventional PCR approach to nucleic acid detection and absolute quantification. Digital PCR works by partitioning a sample of DNA or cDNA into many individual, parallel PCR reactions. Current quantification methods rely on the assumption that the PCR reactions are always able to detect single target molecules. When the assumption does not hold, the copy numbers will be severely underestimated. We developed a novel dPCR quantification method which determines whether the single copy assumption is violated or not by simultaneously estimating the assay sensitivity and the copy numbers using serial dilution data sets. The implemented method is available as an R package "digitalPCR".